2018
DOI: 10.1093/annonc/mdy239
|View full text |Cite
|
Sign up to set email alerts
|

Now the dust has settled over immune checkpoint blockade in metastatic prostate cancer

Abstract: Selected ongoing trials for patients with castration-resistant prostate cancer currently recruiting or awaiting results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, the PD-1 inhibitor pembrolizumab shows antitumor activity in patients with evidence of progression on enzalutamide [58] and in the docetaxelrefractory setting (Keynote-199 trial; NCT02787005). Several trials with immune checkpoint inhibitors as a single agent treatment or as combination therapy are currently ongoing in both unselected as in immunogenic subtypes, such as those harboring microsatellite instability, high tumor mutational load or biallelic inactivation of CDK12 or BRCA2 [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, the PD-1 inhibitor pembrolizumab shows antitumor activity in patients with evidence of progression on enzalutamide [58] and in the docetaxelrefractory setting (Keynote-199 trial; NCT02787005). Several trials with immune checkpoint inhibitors as a single agent treatment or as combination therapy are currently ongoing in both unselected as in immunogenic subtypes, such as those harboring microsatellite instability, high tumor mutational load or biallelic inactivation of CDK12 or BRCA2 [59].…”
Section: Discussionmentioning
confidence: 99%
“…An important feature of prostate cancer is the low tumor mutation burden and thus diminished neoantigen expression compared with many other cancers 104 . Only 10–30% of unselected patients respond to PD-1/PD-L1 blockade 105 . However, a recent study investigated 1551 prostate tumors and found that 32 (3.1%) prostate cancer specimens were associated with MSI-H molecular phenotype and high tumor mutation burden.…”
Section: Introductionmentioning
confidence: 99%
“…Above all, the mCRPC state of prostate cancer is considered an immunologically cold malignancy, , rendering the body’s immune system ineffective in suppressing tumor growth. Clinical trials evaluating FDA approved cancer immunotherapies have been undertaken to address this escape mechanism. , Pembrolizumab ( anti -PD-1) provided a median survival of 7.9–14.1 months depending on patient cohort selection criteria . Other immune checkpoint inhibitors such as ipilimumab ( anti -CTLA-4) fail to increase overall survival in mCRPC patients .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials evaluating FDA approved cancer immunotherapies have been undertaken to address this escape mechanism. 3,4 Pembrolizumab (anti-PD-1) provided a median survival of 7.9−14.1 months depending on patient cohort selection criteria. 5 Other immune checkpoint overall survival in mCRPC patients.…”
Section: ■ Introductionmentioning
confidence: 99%